Context-specific “silver-spoon” effects of wetlands, climate, and temperature on lifetime fitness in a short-lived temperate-breeding migratory songbird - Berzins, Lisha L.; Dawson, Russell D.; Clark, Robert G. (Frontiers in Bird Science, 2024)
Drivers of global change are creating strongly contrasting early life conditions for developing offspring, which may have carry-over effects on lifetime fitness. We tested for "silver-spoon" effects of natal conditions (environmental conditions and maternal quality) and individual quality (pre-fledging) on the lifetime reproductive success (LRS) of aerial insectivorous adult tree swallows (Tachycineta bicolor) hatched in distinct populations with contrasting environments in Saskatchewan and British Columbia, Canada. In both populations, LRS of adults was influenced by environmental conditions they experienced as developing nestlings, but silver-spoon effects were context-dependent, indicating population-specific responses to the local environment.Higher natal temperature in Saskatchewan had positive silver-spoon effects on the LRS of adult swallows, but the opposite was observed in British Columbia, likely because the highest temperatures local recruits experienced as nestlings occurred during heat extremes. In Saskatchewan, where wetter conditions reflect higher wetland abundance and food supply, we detected a negative effect of good natal wetland conditions on adult LRS, contrary to our hypothesis. However, since current breeding wetland conditions are a strong driver of adult fitness, and adults experiencing high natal wetland abundance generally bred when wetland abundance was lower, we suspect any potential benefits of natal wetland abundance on LRS were overridden by wetland conditions during breeding. As hypothesized, wetter natal conditions in British Columbia, which reflect an unfavourable environment for developing nestlings, had negative silver-spoon effects on the LRS of adults. No maternal or pre-fledging quality effects were detected at either site. Therefore, LRS of individuals within distinct populations is influenced, at least in part, by carry-over effects of the natal environment that vary locally.Consequently, natal environmental conditions that affect fitness, with putative population-level consequences, may underly spatially-varying population trends of regionally distinct populations within a species' range.